Equal but inequitable: Who benefits from gender-neutral tenure clock stopping policies? - Antecol, Heather; Bedard, Kelly; Stearns, Jenna (The American economic review, 2018)
Many skilled professional occupations are characterized by an early period of intensive skill accumulation and career establishment. Examples include law firm associates, surgical residents, and untenured faculty at research-intensive universities. High female exit rates are sometimes blamed on the inability of new mothers to survive the sustained negative productivity shock associated with childbearing and early childrearing in these environments. Gender-neutral family policies have been adopted in some professions in an attempt to “level the playing field.” The gender-neutral tenure clock stopping policies adopted by the majority of research-intensive universities in the United States in recent decades are an excellent example. But to date, there is no empirical evidence showing that these policies help women. Using a unique dataset on the universe of assistant professor hires at top-50 economics departments from 1980–2005, we show that the adoption of gender-neutral tenure clock stopping policies substantially reduced female tenure rates while substantially increasing male tenure rates. However, these policies do not reduce the probability that either men or women eventually earn tenure in the profession.